1994
DOI: 10.1111/j.1600-0625.1994.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Human dermatophyte‐responsive T‐cell lines recognize cross‐reactive antigens associated with mannose‐rich glycoproteins

Abstract: Resistance to dermatophyte infections has been shown to be mediated in part by T lymphocytes. The dermatophyte antigens recognized by human T lymphocytes and their degree of cross-reactivity were analyzed. Dermatophyte-responsive T-cell lines were generated by in vitro sensitization to crude fungal extracts obtained from Trichophyton rubrum, Trichophyton tonsurans, Microsporum canis and Epidermophyton floccosum. Proliferation was measured by incorporation of 3H-thymidine. The human T-cell lines responded to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This finding is in accordance with previous studies demonstrating that T. rubrum can produce substances that diminished the immune response 42–44 . Therefore T. rubrum is one of the most common causes of dermatophytosis in humans, accounting for more than 90% of chronic human’s cases 1 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with previous studies demonstrating that T. rubrum can produce substances that diminished the immune response 42–44 . Therefore T. rubrum is one of the most common causes of dermatophytosis in humans, accounting for more than 90% of chronic human’s cases 1 .…”
Section: Discussionsupporting
confidence: 93%
“…23 The potential iatrogenic and immunologic implications of onychomycosis, carrying a large fungal load, remains to be investigated; however, it has been reported that T. rubrum infection may suppress cell‐mediated immunity. 24–26 Onychomycosis has a particular impact on certain population groups such as the elderly, HIV‐infected patients, 27–30 and in those with concomitant diabetes mellitus. 31 Onychomycosis patients harbor a large fungal load and from an epidemiologic viewpoint may be a source of infection for other people as well as for reinfection for tinea manuum and pedis.…”
Section: Effects Of Onychomycosismentioning
confidence: 99%
“… 25 Trichophytin can elicit a specific lymphoproliferative response, although it yields predominantly T‐suppressor cells. 26 Although cell‐mediated immune reactions may be suppressed by T. rubrum , the humoral response generally remains intact and antibodies of different classes have repeatedly been demonstrated. Recently, Trichophyton ‐specific immunoglobulin E (IgE) antibodies were found in patients with T. rubrum infections.…”
Section: Effects Of Onychomycosismentioning
confidence: 99%
“…In a dose-dependent manner, TRM are able to inhibit in vitro lymphoproliferative response of mononuclear leukocytes in response to several antigens (dermatophytic or not) and mitogens (Blake et al 1991a, b); paradoxically, they are a major T-cell antigen (MacCarthy et al 1994). They include lymphocyte inhibition by cell-wall mannans, macrophage function alteration, differential activation of keratinocytes and, putatively, differential secretion of proteases.…”
Section: Pathogenesis and Innate Immunitymentioning
confidence: 99%